Construction of Biopore Holes in the KTH Office Environment Mahakam Delta, Muara Jawa Ulu: Pembuatan Lubang Biopori di Lingkungan Kantor KTH Delta Mahakam Muara Jawa Ulu - Darnah Darnah; Hepi Purwanto; Rizqi Abdhi Mulawarman; Aan Nugraha; Sudirman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2026)
Muara Jawa Ulu Village is one of the villages in Muara Jawa District, Kutai Kartanegara Regency, East Kalimantan. This village is characterized by residential areas, agricultural land, and some plantation areas or community businesses. Its location in the lowlands offers considerable potential for natural resources but also causes environmental problems, such as waterlogging and the accumulation of organic waste. To address these problems, Mulawarman University Community Service (KKN) students implemented a program to create Biopore Infiltration Holes (LRB) in the Delta Mahakam Forest Farmers Group (KTH) Office. This program aims to increase water absorption into the soil, process organic waste into useful compost, and raise public awareness of the importance of sustainable environmental conservation. This activity was carried out through several stages: coordination, socialization, drilling vertical holes to a depth of ± 100 cm, filling with organic waste such as dry leaves and kitchen scraps, and providing education and mentoring to KTH members. The results of the implemented activities demonstrate that biopore holes are highly effective in reducing waterlogging during rainstorms. By utilizing organic waste to create natural compost, they can improve the cleanliness and aesthetics of the environment around the office. The educational impact is also evident in the increased public understanding of the importance of environmentally friendly technology. Furthermore, KTH members expressed interest in replicating this technology independently in their homes and on their land. This program demonstrates that simple, inexpensive technologies like biopore holes can be a real solution to local environmental challenges and directly improve the community's quality of life.